2010
DOI: 10.1186/1744-9081-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Myotonic Dystrophy type 1: clinical and neuronal correlates

Abstract: BackgroundThis study was designed to investigate the prevalence and correlates of depression in Myotonic dystrophy type 1 (DM1).MethodsThirty-one patients with DM1 and 47 subjects in a clinical contrast group, consisting of other neuromuscular disorders, including Spinal muscular atrophy, Limb girdle muscle atrophy and Facioscapulohumeral dystrophy, completed Beck Depression Inventory (BDI). We aimed to establish whether different factors associated with DM1 correlated with ratings in the BDI.ResultsSigns of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
60
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 36 publications
10
60
4
Order By: Relevance
“…Such white and grey matter alterations do not seem to be depictable by means of transcranial sonography. On the other hand, clinical symptoms and signs seem to indicate preferential involvement of distinct regions, since attention deficits, daytime sleepiness, depression and restless legs are common features in DM1 and DM2 [12,13,32]. With regard to the correlation of brain morphological alterations to these CNS syndromes, MRI studies revealed inconsistent findings [1][2][3].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Such white and grey matter alterations do not seem to be depictable by means of transcranial sonography. On the other hand, clinical symptoms and signs seem to indicate preferential involvement of distinct regions, since attention deficits, daytime sleepiness, depression and restless legs are common features in DM1 and DM2 [12,13,32]. With regard to the correlation of brain morphological alterations to these CNS syndromes, MRI studies revealed inconsistent findings [1][2][3].…”
Section: Discussionmentioning
confidence: 87%
“…Depressive symptoms are frequent in DMs [1,12]. The cause of depression in DMs is still unclear, as some authors explain depression as a psychological reaction to the chronic disease, and others as a direct consequence of structural CNS alterations [41,42].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(10) For others, personal factors such as denying their symptoms or feeling too proud to seek medical advice influenced their delay in getting their symptoms checked out: I am a relatively private person when it comes to medical problems so I didn't really say to anyone about it. (11) Delays in having symptoms recognised or taken seriously by medical professionals and in accessing specialist referrals were also commonly discussed:…”
Section: Sharing Diagnosis Experiencesmentioning
confidence: 99%